Historical and philosophical principles of creating a model of the most recent (sensitive) information policy of Ukraine as a European state - Holovanova , Natalia (Theory and Practice of Public Administration, 2019)
The problems of functioning of the traditional model of public administration in Ukraine and new threats of the aggressive external environment in the face of the state's information policy are considered. The vids of the traditional model of public administration, reinforced by the fact that they are further distortedly implemented, and the need for the transformation of traditional approaches are indicated.The content of national values, interests and goals in the information sphere is analyzed. Ukraine's national interests in the information sphere such as observance of constitutional rights and freedoms of people in the ability to obtain information, preservation and strengthening of values, representing Ukraine in the international environment and informing Ukrainian citizens about state information policy, development of modern information technologies, protection of information resources are represented according to the Doctrine of Information Security of Ukraine.  Value added information policy is stated as very important.The main laws that define the media space and information policy of the state of the new years are introduced. It is emphasized that the principles of creating the newest model defined as anthropocentric, that is, we take it as a basis the fact that man is the center of the universe and the purpose of all events that it has been designed and created by God in His image and likeness are the philosophy of Kyivan Rus and international law. Ancient sacred books such as the Bible (XV century BC - I century AD), Tanah, the Koran, the Tristarians (Pali canon), Vedi, V-Jing, Dao Zang and Chuang-tzu are noted as the first sources and the first legislators.The implementation of basic values ​​in the state creation of Ukraine in the genesis is presented. Kyiv centrism, Jerusalem centrism which was at the same time theocentrism, theocentric model of the world and cordocentrism clearly expressed in The Legend of Boris and Hlib are defined as principles of the East Slavic world because of transcendental and sacredness, eternity and superstructure.Kyiv itself, as the capital, that cements the unity of the state and provides harmonious coexistence of the regions of Ukraine, gives the mental field, the media space of the country the national spiritual and aesthetic qualities inherent in the best personalities and embodied in the best examples of science and art is proved as state-creating center. Kyiv is shown as a possible model for the latest, effective governance, in particular a well-balanced regional policy.It is told that in the Association Agreement, the European Union and Ukraine declared mutual respect for common values, among which are particularly important: democratic principles; Rule of Law; effective management; Human Rights; fundamental freedom. A diversity of European cultures, tolerance, individual freedom, the problems (xenophobia, minorities, intolerance, the environment, drugs, crime, foreign aggression, etc.) are accented.The importance of joint projects within the framework of the Framework Program of Ukraine-Ukraine CoE and EU for 2014-2017 such as the Freedom of Media in Ukraine project is proclaimed. Successful implementation in 2014-2017 by regulators actions to provide broadcasters and software service providers information on the structure of media ownership (transparency of media ownership), broadcasting of territorial communities, public broadcasting, digital broadcasting, information security measures given in the article proved the proclamation.Presentation in April 2019 of a scientific monograph by E. Afonin and A. Martynov "Ukrainian miracle. From Depression to Social Optimism" with the results of historical and sociological studies of Ukrainian scientists in 1992-2018 is made public.The importance of applying evidence-based policy in modern times, the introduction of dialogue and rhetoric of peace, non-violence and humanity in society are determined. The significant influence of the features of the global media space and the newest reality on the principles of information policy is emphasized. The main approaches of the newest (sensitive) information policy in Ukraine such as- universal international legal regulation of media space;- provision of high-quality content of television and radio programs, participation in theprograms of scientists, experts;- elimination of stereotypes; rhetoric of peace and humanity, introductionpolitics of nonviolence in the society, cross-linking of the country; consensus orientation; All-Ukrainian, All-European and World Dialogue;- development of translation activities and inclusion in the List adapted for broadcasting in Ukraine television and radio programs, films of the countries of the European Union and Asian countries of the world;- development of cultural and educational space as a part of social space, the universal humanitarian education; recognition by universities and academies of the status of centers of knowledge and sources of innovative ideas in society;- putting into practice the principles of New Public Governance, Good Governance, curbs of totalitarian methods and approaches in information policy, the introduction of subjective-subjective social relations, the transition from the web of hierarchical connections to the network of interconnections and the power of creativity;- appeal to national memory, to the philosophical ideas of Kyivan Rus, to the ideas of travel, cordocentrism and openness;- attention to the context of events, texts, statements; - overcoming the enthusiasm of lawmaking;- recognition of truth as the basis of a humanistic world outloo, - are offered.